2018
DOI: 10.3103/s1068367418030096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Garlic on the Economical and Physiological Characteristics of Broiler Chickens

Abstract: The aim of this investigation was to evaluate the beneficial effects of garlic powder as a phytogenic supplement on broilers chickens' performance. The assumption that garlic could improve some economic and performance characteristics of broiler chickens (i.e. body weight, feed intake, water intake, feed conversion ratio, feeding cost, carcass yield and mortality rate) was tested. A total of 400 one-day-old chicks of mixed sex (Hybrid) were weighed and randomly assigned to four treatment groups, each with 4 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
1
8
1
Order By: Relevance
“…These findings are consistent with those of [19]. Similarly, when comparing the birds-fed garlic powder diets to the control group, [7] found that feed intake was considerably (P<0.05) more excellent in the birds-provided garlic powder diets. Garlic powder supplementation enhances feed intake, most likely due to the associated flavor element.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with those of [19]. Similarly, when comparing the birds-fed garlic powder diets to the control group, [7] found that feed intake was considerably (P<0.05) more excellent in the birds-provided garlic powder diets. Garlic powder supplementation enhances feed intake, most likely due to the associated flavor element.…”
Section: Resultssupporting
confidence: 92%
“…Allicin can be used as a natural antibiotic since it is more effective than penicillin and tetracycline at eliminating pathogenic bacteria [6]. Garlic has been utilized to promote growth by improving poultry performance [7].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that supplementation of garlic to broilers' diets improved their immune systems and digestion efficiency due to the abundance of bioactive compounds of garlic, namely, alliin, daily lsulphide and allicin [41]. Additionally, improvement in weight gain and better FCR of broiler chickens following the dietary supplementation of garlic can be attributed to allicin-active ingredients that promote the beneficial microflora in the gut, thereby improving the digestion efficiency and enhancing the energy utilization [42,43]. Peinado et al [44] found that the compounds obtained from garlic had increased digestibility and activities of intestinal mucosal enzymes, confirming their application as alternatives to antibiotics in broiler nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The used antibiotics leave residues on animal products and cause resistance of microorganisms to antibiotics and this resistance can be transferred from one microorganism to another and from one antibiotic to another and thus used in the treatment of diseases cross-resistance to antibiotics (Braykov et al, 2016;Özkan et al, 2007). Therefore, the modern trend is to replace chemical antibiotic growth promoters with some natural growth promoters such as medicinal and aromatic plants powder, medicinal and aromatic plant extracts, probiotics and enzymes (Bednarczyk et al, 2016;Al-Massad et al, 2018;Mondal et al, 2015). Phytogenic growth promoters have a beneficial effect on gut health for optimum function.…”
Section: Introductionmentioning
confidence: 99%